HAKIKAT ILMU PENGETAHUAN DALAM ISLAM (Analisis Filosofis Dan Implikasinya) - alfaruki, achmad (Universitas Nahdlatul Ulama Surakarta, 2024)
Humans are perfect creatures created by Allah SWT. This perfection is in the form of reason and the carrying capacity of the other senses. With this perfection, it is human beings who are tasked with being caliphs on this earth. As caliphs, humans strive to create a civilization of life that continues to develop continuously. To support this civilization, humans need science and knowledge. Science and knowledge emerge with the existence of the human mind, which has been gifted by Allah SWT. This study employs a library-based approach. The results of the research analysis were taken from primary data as the main source, namely a book entitled